Las enfermedades emergentes transmitidas por vectores:: Paludismo, Dengue, Chikungunya y Zika - Alfaro-Martínez, Carlos Roberto; Saldaña-Torres, Daniel Rafael; Godínez-Ríos, Miguel Guadalupe; Verde-Millán, Julio Cesar; Trujillo-Rodríguez, Gerardo de Jesús; López-Rodríguez, Martha Patricia; Martínez-de-Villarreal, Laura Elia; Flores-Suarez, Adriana Elizabeth; Ponce-García, Gustavo; Rodríguez Sánchez, Iram Pablo (Biología y Sociedad, 2018)
Vectors are animals that transmit pathogens, including parasites, from one person (or animal) infected to another one and they cause serious diseases in humans. These emerging and re-emerging diseases represent a serious public health problem. WHO collaborates with partners to disseminate knowledge and raise awareness so that people know how to protect themselves and their communities against these vectors. To date, diseases such as Dengue, Malaria, Chikungunya, and Zika continue to affect a large part of the world population, so it is important to have knowledge about the generalities of these diseases as well as how to identify and avoid them